2012
DOI: 10.1371/journal.pone.0043326
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Responses following Exposure to Modulated Radiation Fields

Abstract: During the delivery of advanced radiotherapy treatment techniques modulated beams are utilised to increase dose conformity across the target volume. Recent investigations have highlighted differential cellular responses to modulated radiation fields particularly in areas outside the primary treatment field that cannot be accounted for by scattered dose alone. In the present study, we determined the DNA damage response within the normal human fibroblast AG0-1522B and the prostate cancer cell line DU-145 utilisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 28 publications
6
51
0
Order By: Relevance
“…We have shown that a radiation field with many high dose gradients may have an advantage over a uniform field [2], because it is more lethal to cancer cells than to normal cells. We attribute this effect predominantly to the production, diffusion and response to radiation induced bystander signals, which is consistent with previous reports of up to 60% of cell death following irradiation being attributed to bystander effects [3,4].…”
supporting
confidence: 92%
“…We have shown that a radiation field with many high dose gradients may have an advantage over a uniform field [2], because it is more lethal to cancer cells than to normal cells. We attribute this effect predominantly to the production, diffusion and response to radiation induced bystander signals, which is consistent with previous reports of up to 60% of cell death following irradiation being attributed to bystander effects [3,4].…”
supporting
confidence: 92%
“…We have shown that a radiation field with many high dose gradients may have an advantage over a uniform field [2], because it is more lethal to cancer cells than to normal cells. We attribute this effect predominantly to the production, diffusion and response to radiation induced bystander signals, which is consistent with previous reports of up to 60% of cell death following irradiation being attributed to bystander effects [3,4].The use of a radiation field that delivers a non-uniform dose with high dose gradients is not new. Spatially fractionated radiotherapy or grid therapy, delivers radiation through a collimating grid block or by using the multileaf collimator of a linear accelerator.…”
supporting
confidence: 90%
“…DNA damage responses following exposure to modulated radiation fields was evaluated. [50] A fibroblast cell line AG-1522B and prostate cancer cell line DU-145 was shielded 25, 50 and 75% from a dose of 1Gy to measure 53BP1 and γ-H 2 AX foci at 2mm intervals. The study reported an observation of out-of-field foci compared to the controls.…”
Section: Various End Points Of Radiation Induced Bystander Effects Inmentioning
confidence: 99%